A emergência do riso como enunciado - Sousa, Waldênia Klésia Maciel Vargas (2017)
The thesis The emergence of laughter as an enunciated analyzes laughter as an enunciative materiality in the light of the studies concerning Discourse Analysis in the French dimension (PÊCHEUX, 1988; 1990a; 1990b), referring to Michel Foucault (2009a; 2009b; 2009c; 2010) and Mikhail Bakhtin (2003; 2006). In this research, we particularly mobilize the notion of enunciation as a not verbal materiality that can be interpreted by the subjects and produces meaningful effects in given socio-historical conditions. We also reflect on the notions of discourse, discursive formation, knowledge, power, subject, truth effect and how these notions relate to the analysis of the not verbal material that is laughter. We refer to the studies that deal with the historical course and delineate the discursive functions of laughter, with emphasis on the studies conducted by Minois (2003), Alberti (2002) and Bremmer and Roodenburg (2000). The corpus was collected on the Internet, from 2014 to 2017, and consists of laughter concerning religious discourse, politics and the judiciary. In these discourses, we observe forms of laughter that reverberate in the social body due to enunciative rarity, discursive order disobedience and the rules of formation of these fields of knowledge, as well as cheerful, cordial and ironic laughter, the latter three emerging frequently in the day-to-day life and constituting the discursive memory of the subjects. The analyses chapter attempts to verify how laughter relates to enunciations that constitute the associated field and permeate the exercise of the enunciative function. We find that the irruption of this not verbal statement can modify the sense effect of a verbal enunciation and can respond to both verbal texts and not verbal enunciations, constituting a responsive attitude to other enunciations, such as the node in the discursive network. Laughter also functions as an exercise power that emerges to ridicule the collocutor or the subject of the enunciation as a strategy of public persuasion. Thus, among the functions observed in the collected laughter, we emphasize the derisory function, the cordiality effect, the relationship between laughter and madness and resistance to the rules of discourse formation in which seriousness is understood as normality and laughter is disrespectful. Likewise, the laughter that emerges in enunciation builds the intericonic network of images that, in turn, constitute the discursive memory of the subjects, enabling the dialogue between laughter images that we can recognize and interpret in discursive processes, allowing for laughter to be analyzed as an enunciation